The origin of the elements from periodic table - Horvath, Jorge Ernesto (Cadernos de Astronomia, 2022)
We present in this article a broad overview of nucleosynthesis of cosmological, stellar and catastrophic origin, which lead to populate the Periodic Table of elements created by D. Mendeleev more than a century ago.